REFÓRMESE EL ART.151 DEL CODIGO ORGANICO INTEGRAL PENAL ECUATORIANO, PARA QUE ARMONICE CON EL ART.1 DE LA CONVENCION CONTRA LA TORTURA Y OTROS TRATOS O PENAS CRUELES, INHUMANOS O DEGRADANTES, REFERENTES A REFORZAR LA DEFINICION DEL TERMINO TORTURA - CASTILLO ARMIJOS, JORDY STEVEEN (2016)
For the protection of human beings, to avoid actions that might interfere with the freedoms, fundamental rights and human dignity, created Human Rights are universal legal guarantees protecting individuals. Defining the relationship between individuals and the structures of power, especially the state. It is the duty of every State to legislate on human rights, fulfilling certain duties, establishing certain prohibitions. From the legal point of view, can be defined as all individual and collective rights recognized by the States in their constitutions and in international law. In our country there are not enough rules to prevent and punish international crimes against humanity of torture, resulting in a legal vacuum, the absence of a definition that fits the events. This lack of legislation, not only means a negligent act of our Assembly members, but also a flagrant violation of Art. 84 of the Constitution of the Republic of Ecuador, which requires anybody with regulatory powers required to adapt formal and materially, the laws and other legal norms to the rights provided in the Constitution and international treaties, and those necessary to ensure the dignity of human beings or communities, peoples and nationalities, making it necessary to appeal to legislators to classification, helping in efforts to demand genuine reforms. Torture as a social phenomenon has been studied as a concept, as a category and as a theory, why has concerned man since ancient times to give a definition and conceptualization, that this in turn is applied as typing in different legislation in the world. A torture I've studied from concept stated in our criminal law, constitutional and not rather from international agencies. Concluding that no person should be deprived of their human rights, these being inalienable, and, waived, or should be removed, except in exceptional situations and according to due process being interrupted right of a person to freedom when a court convicted of a crime with the penalty.